PENGETAHUAN KONTEN PEDAGOGI (PCK) DAN URGENSINYA DALAM PENDIDIKAN GURU - Purwianingsih, Widi; Rustaman, Nuryani Y.; Redjeki, Sri (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2010)
A serius effort to reach students aspects of content, syntactically and substantively, will not be achieved without being accompanied by the knowledge of teaching strategies adopted appropriate by the teachers. Teachers should understand and be able to integrate content knowledge into knowledge about the curriculum, learning, and especially students. Such knowledge is expressed as Pedagogical Content Knowledge (PCK). To identify and assess developments of their PCK, a teacher needs a rich conceptual understanding as well as integrate with expertise in using teaching procedures, strategies and approaches, to be implemented in the classroom. PCK is considered as a strategic answer for transforming of content/subject matter into a form of presentation in the classroom. Because of PCK is one of the main components in teaching, to produce qualified teachers, equip ability PCK becomes a crucial thing to be done by the teacher-producing institutions. This is due to the PCK is important in improving teaching and learning process which aims to provide [a] better understanding of students. PCK is as important as knowledge about subject matter which is used as the subject of any learning process. Without PCK, the process of transformation of a subject matter in the effort to construct students' knowledge, will not take place very well.